Application of Tween 80 and Tween 20 for microwave-assisted extraction of oxyresveratrol from mulberry (Morus alba L.) twigs - Raditya Iswandana, Sintha Olisia, Mitha Adriyani, Mahdi Jufri, Abdul Munim (Journal of Applied Pharmaceutical Science, 2020)
Oxyresveratrol is a polyphenolic compound found in Mulberry (Morus alba L.) twigs and has known as a skin-lightening agent. Many methods can be applied to extract oxyresveratrol from Mulberry twigs. This research aimed to optimize the extraction method by using surfactant Tween 80 and Tween 20-based microwave-assisted extraction (MAE). Extraction parameters, including solvent concentration, liquid–solid ratio, and extraction time for oxyresveratrol, were optimized using response surface methodology based on Box–Behnken Design. This research also extracted the oxyresveratrol by maceration, and then the oxyresveratrol content from each extraction method was compared. Oxyresveratrol content was determined using high-performance liquid chromatography (HPLC). For Tween 80, the optimum condition was obtained at 10.5 mM, 30:1 ml/g liquid–solid ratio, and 10 minutes extraction time. For Tween 20, the optimum condition was obtained at 100 mM, 40:1 ml/g liquid–solid ratio, and 5 minutes extraction time. Oxyresveratrol content was 0.0146 mg/g dried sample and 0.0172 mg/g dried sample at the optimum condition of Tween 80 and Tween 20 surfactant, respectively. Meanwhile, the oxyresveratrol content of the maceration method with 96% ethanol was 1.5704 mg/g dried sample. In conclusion, these results show that the application of Tween 80 and Tween 20 as solvents for MAE of Oxyresveratrol from mulberry twigs was not fully successful since other extraction conditions should be considered, such as temperature, pH, and microwave energy.
Keywords: Microwave-assisted extraction (MAE), Morus alba, oxyresveratrol, surfactant, Tween 20, Tween 80.